2014
DOI: 10.1097/iae.0000000000000147
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells and Response to Ranibizumab in Age-Related Macular Degeneration

Abstract: The observations indicate responsiveness of circulating EPCs to the CNV process in AMD. They suggest the hypothesis that increased stromal cell-derived factor 1 production at the CNV site (reflected in higher plasma levels) recruits EPCs from the circulation, and that antivascular endothelial growth factor therapy selectively decreases the recruitment of cells to be incorporated into new vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
0
9
3
Order By: Relevance
“…; Scotti et al. ). The authors suggest that this phenomenon is the result of a chronic vascular dysfunction which may be associated with RPE ischaemia as a key element in the pathogenesis of AMD.…”
Section: Discussionmentioning
confidence: 98%
“…; Scotti et al. ). The authors suggest that this phenomenon is the result of a chronic vascular dysfunction which may be associated with RPE ischaemia as a key element in the pathogenesis of AMD.…”
Section: Discussionmentioning
confidence: 98%
“…Four small case-control studies have investigated the plasma levels of stromal cell-derived factor 1 in AMD patients with mixed results. Two studies, by the same group, report significantly lower levels of stromal cell-derived factor 1 in patients with nAMD, 210,211 whereas another study showed the inverse effect, 299 and the fourth did not report any differences between nAMD and control individuals. 115 298 Silva et al, 2012 312 Smailhodzic et al, 2012 319 Guymer et al, 2015 120 Reynolds et al, 2009 278 Ansari et al, 2013 14 Sharma et al, 2013 308 Sharma et al, 2013 310…”
Section: Chemokines and Chemokine Receptorsmentioning
confidence: 92%
“…Four studies detected significantly upregulated levels of VEGF in serum or plasma, 6,115,205,338 but these findings are contrasted with 10 other studies that reported no association. 41,80,112,122,125,211,231,299,353,380 VEGF signaling is mediated through a complex of receptors and coreceptors, of which the soluble form of VEGF receptor 1 has been investigated in a number of studies. As in the case of VEGF, these studies do not offer a clear direction of effect.…”
Section: Vascular Endothelial Growth Factor and Soluble Vegf Receptormentioning
confidence: 99%
“…1 CNV is a complex process, and tissue ischemia is thought to be involved in its development. 2 There is accumulating evidence that not only angiogenesis but also vasculogenesis participates in the development of CNV 3,4 -the peripheral blood contains a population of bone marrowderived endothelial progenitor cells (EPC) that can differentiate into endothelial cells.…”
mentioning
confidence: 99%